Migraine-Related Stigma and Its Relationship to Disability, Interictal Burden, and Quality of Life - Shapiro, Robert E; Nicholson, Robert A; Seng, Elizabeth K; Buse, Dawn C; Reed, Michael L; Zagar, Anthony J; Ashina, Sait; Muenzel, E Jolanda; Hutchinson, Susan; Pearlman, Eric M; Lipton, Richard B (Neurology, 2024)
This population-based analysis characterizes the relative frequency of migraine-related stigma and its cross-sectional relationship to migraine outcomes. We hypothesized that migraine-related stigma would be inversely associated with favorable migraine outcomes across headache day categories. OVERCOME (US) is a web-based observational study that annually recruited a demographically representative US sample and then identified people with active migraine using a validated migraine diagnostic questionnaire. It also assessed how frequently respondents experienced migraine-related stigma using a novel 12-item questionnaire (Migraine-Related Stigma, MiRS) that contained 2 factors; feeling that others viewed migraine as being used for Secondary Gain (8 items, α = 0.92) and feeling that others were Minimizing disease Burden (4 items, α = 0.86). We defined 5 groups: (1) MiRS-Both (Secondary Gain and Minimizing Burden often/very often; (2) MiRS-SG (Secondary Gain often/very often); (3) MiRS-MB (Minimizing Burden often/very often); (4) MiRS-Rarely/Sometimes; (5) MiRS-Never. Using MiRS group as the independent variable, we modeled its cross-sectional relationship to disability (Migraine Disability Assessment, MIDAS), interictal burden (Migraine Interictal Burden Scale-4), and migraine-specific quality of life (Migraine Specific Quality of Life v2.1 Role Function-Restrictive) while controlling for sociodemographics, clinical features, and monthly headache day categories. Among this population-based sample with active migraine (n = 59,001), mean age was 41.3 years and respondents predominantly identified as female (74.9%) and as White (70.1%). Among respondents, 41.1% reported experiencing, on average, ≥4 monthly headache days and 31.7% experienced migraine-related stigma often/very often; the proportion experiencing migraine-related stigma often/very often increased from 25.5% among those with <4 monthly headache days to 47.5% among those with ≥15 monthly headache days. The risk for increased disability (MIDAS score) was significant for each MiRS group compared with the MiRS-Never group; the risk more than doubled for the MiRS-Both group (rate ratio 2.68, 95% CI 2.56-2.80). For disability, interictal burden, and migraine-specific quality of life, increased migraine-related stigma was associated with increased disease burden across all monthly headache day categories. OVERCOME (US) found that 31.7% of people with migraine experienced migraine-related stigma often/very often and was associated with more disability, greater interictal burden, and reduced quality of life.